Penerapan Program Home Care Melalui Senam Lansia Untuk Mengurangi Nyeri Sendi Dan Meningkatkan Fungsi Gerak: Implementation of a Home Care Program through Elderly Exercise to Reduce Joint Pain and Improve Motor Function - Nilawati, Nilawati; Padang, Alisarjuni; Hasibuan, Bulqis P.; Sihombing, Cindy Laura Margareth; Anissa F, Fahira; Gulo, Widya Jerni (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Aging is a natural biological process that leads to a decline in physiological functions, particularly in the musculoskeletal system, making older adults more susceptible to joint pain and limitations in functional mobility. A home care approach through non-pharmacological interventions such as elderly exercise is needed as a promotive and preventive effort to maintain independence and quality of life among older adults. This study aimed to implement a home care program through education and practice of elderly exercise to reduce joint pain and improve functional mobility in older adults. The method used was a pre-experimental design with a one-group pretest–posttest approach, conducted through educational, participatory, and applicative strategies that included the stages of preparation, implementation, and evaluation. The participants consisted of 35 older adults aged 60–75 years in Hamlet I, Tanjung Anom Village, Deli Serdang Regency. The intervention involved health education and elderly exercise practice for 15–20 minutes, consisting of warm-up, core movements, and cool-down sessions. Evaluation was carried out by measuring joint pain levels using the Numeric Rating Scale (NRS) and functional mobility using activities of daily living (ADL/IADL) assessments. The results showed a reduction in joint pain levels from moderate to mild and an improvement in functional mobility, as indicated by increased independence of older adults in performing daily activities. It was concluded that the implementation of a home care program through elderly exercise was effective in reducing joint pain and improving functional mobility, and it is recommended to be applied sustainably at the community level with the support of families and health cadres.